KAJIAN HUKUM TERHADAP PELANGGARAN KODE ETIK JAKSA DALAM TINDAK PIDANA KORUPSI - Alicia Andromeda Sanyoto; Amelia Febriyanti; Bulan Natalia; Rachel Milafebina Sembiring; Sandra Dwi Putri Pahlawan; Jeane N Saly (STKIP Bina Bangsa Meulaboh, 2023)
The violation of the code of ethics among prosecutors is increasing, and there are various underlying factors contributing to these violations. One of the violations of the code of ethics is engaging in corrupt practices. To ensure that prosecutors have personal integrity and high discipline in carrying out their law enforcement duties for the sake of justice and truth, the Indonesian government has issued Regulation of the Attorney General of the Republic of Indonesia Number PER-014/A/JA/11/2012 concerning the Code of Conduct for Prosecutors and other related regulations. The research method used is normative with literature study as the data collection method. The objective is to ensure that the prosecution understands its identity in carrying out its duties as a representative of the state and as a protector of society in the field of law enforcement. By examining the existing regulations, there are sanctions that will be imposed on prosecutors who violate the Code of Ethics or breach their oath or pledge of office based on Law Number 16 of 2004 concerning the Prosecution. The sanctions include dishonorable dismissal from their position.